The proteome of mycoplasma pneumoniae, a supposedly “simple” cell - Catrein, Ina; Herrmann, Richard (Proteomics, 2011)
This review covers progress in proteome research on Mycoplasma pneumoniae made over the last 5 years. This bacterium is one of the smallest known self-replicating bacteria. With fewer than 700 proposed proteins, it is well suited to a comprehensive proteome analysis. While all of the proposed genes are transcribed, thus far 620 proteins, about 90% of the predicted proteome, have been identified experimentally. To study the proteome organization of M. pneumoniae, 178 soluble protein complexes were isolated under non-denaturing conditions by tandem affinity chromatography and their composition determined by SDS-PAGE and mass spectrometry. The 62 homomultimeric and 116 heteromultimeric protein complexes could be classified according to 12 different COG functional categories. The complexes interacted with each other to some extent, forming larger assemblies. Protein complexes that were large enough and had specific structures (e.g. ribosomes or DNA-dependent RNA polymerase) were visible and countable in their natural environment by cryo-electron tomography. In addition to characterization of the soluble complexes, the analysis of the Triton X-100 insoluble fraction has a major role in the elucidation of the cytoskeleton-like structure, because by analogy with eukaryotic cells, almost all of the structural proteins involved in its formation, and enriched sub-cellular structures, can be found in this fraction.